Pertukaran Peran Domestik dan Publik Menurut Perspektif Wacana Sosial Halliday - Umaimah Wahid; Ferrari Lancia (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2018)
The research on the text of television soap opera “Dunia Terbalik” focuses on the construction of the role of women and men. During this time, men are act as heads of families, leaders and breadwinners as regional representation, while women are more described as housewives, unemployed, and active in domestic areas. This study aims to uncover, criticize, and interpret the unusual reality as an interesting phenomenon that often occurs in the society. By using the theory and method of discourse M.K. Halliday and also equipped with an understanding of the role of domestic and public which is the result of social construction that may not be denied. Women have the ability to act as a breadwinner who replace the role that has been dominated by men. while men or husband in the soap opera ‘accept’, because their incapacity financially, they even enjoy the role that seems unfair to women. Men or husbands keep demanding women or wives to perform domestic roles if they are at home.